ANALISA PERFORMA KAPAL KM. CIREMAI DENGAN MODIFIKASI PENAMBAHAN PROPELLER HUB CAPS FIN DENGAN METODE EKSPERIMEN - Suharto, Suharto; Sulaiman, Sulaiman (Vocational School Diponegoro University, 2020)
The various ship propulsion models there are several considerations in the selection to be applied to the ship, such considerations are required in the planning of the ship's propulsion. With the addition of propeller hub caps fin is expected to deliver a flow model that supports the performance of propulsion systems on ship. The purpose to analyzes the best performance of the propeller shaft engine, representing a comparison of fuel consumption efficiency, as well as ship speed based on the addition of propeller hub caps fin on MV. CEREMAI. Method used was conducted experimentally to determine the performance of the ship's engines before and after using energo pro fin (propeller hub caps fin) with sea trial. Result showsÂ 2% reduction in fuel consumption on the portside main engine and 3% starboard main engine. As well as enabling increased operational speed of KM ships. CIREMAI at 12% with the same rpm round. So selection of ship propeller types affects the performance of enegro profin (propeller hub caps fin).